A Prospective, Multicenter, Observational Registry (ReCoRD) on Demography, Molecular Profile, Clinical Features, and Treatment Outcomes in Individuals with Metastatic Colorectal Cancer - Yadav Y, Sunil Kumar; Desai, Rohit; Sopory, Pranav; Dawer, Femina; Mittal, Rajan; Gaurav, Kumar; Rathod, Rahul; Paspulate, Akhila (Asian Pacific Journal of Cancer Care, 2023)
Background and objective: Globally, approximately 20% of newly diagnosed colorectal cancer cases present with metastasis, and 25% develop metastasis later. The 5-year survival rate for patients with metastatic colorectal cancer (mCRC) is less than 20%. While many studies using population-based cancer registries from India are available for various cancers, data on mCRC in India is scarce. The ReCoRD registry aims to gather real-world data on demographics, treatment patterns, and outcomes in Indian patients with mCRC. Materials and Methods: This was a prospective, multicenter, observational study enrolling 1000 participants with mCRC across up to 15 centers for a period of two years. Recruitment ceased two years after the first patient enrollment. A minimum follow-up of 12-18 months was conducted post-enrollment. Data on demographics, clinical features, molecular profile, treatment options, and treatment outcomes were collected from the study sites by investigators. The Kaplan-Meier method was used to analyze survival data, and the median time computed by this method was presented with a 95% confidence interval. Conclusion: While mCRC remains largely incurable, survival rates have improved with the development of newer cytotoxic chemotherapeutic drugs and targeted agents. The ReCoRD registry’s comprehensive data on demographics, tumor characteristics, molecular aspects, treatment, and treatment outcomes in individuals with mCRC can guide clinicians in decision-making and treatment based on Indian patient data.